Correlation of Circulating Dickkopf-1 Level with Sonographic Findings and Radiographic Grading in Primary Knee Osteoarthritis - Adel Ibrahim Azzam; Abdelrahman Mohamed Labib; Abd-Elshafy Ahmed Haseeb; Ahmed Fathy Abd-Elaziz (Journal of Medical Ultrasound)
Background: Osteoarthritis (OA) is a frequently complex joint disease that involves all joint components, including cartilage degeneration and new bone development. Dickkopf-1 (Dkk-1) regulates bone growth and repair in OA. The purpose of this study is to determine Dkk-1 blood levels in individuals with primary knee joint OA, as well as their associations with disease progression and severity. Methods: This study included 45 individuals with primary OA of the knee and 45 healthy participants. Demographic data, body mass index, Visual Analog Scale, and Western Ontario and McMaster Universities Arthritis questionnaire scores were gathered. On radiography, the Kellgren and Lawrence score was acquired. The knee joint ultrasonography results were documented. The blood level of Dkk-1 was determined using the enzyme-linked immunosorbent assay method. Results: Dkk-1 levels in the blood were substantially higher in patients with OA than in healthy persons. Serum Dkk-1 levels appeared to have a significantly inverted relationship with radiological OA grades in knee OA (P < 0.001). Dkk-1 serum levels were significantly lower in individuals with ultrasonographic knee effusion (median = 3.2, interquartile range [IQR] = 3.1–4.16) than in those without effusion (median = 4.79, IQR = 4.04–5.09). Furthermore, there was a strong correlation between Dkk-1 levels and ultrasonographically measured femoral cartilage thickness. Conclusion: Dkk-1 is an interesting radiological indicator associated with degenerative articular joint disease. It may have a crucial function in slowing the process of degeneration in knee OA and reflecting the disease’s radiographic and clinical severity.